Design of LDPC code for uncorrelated Rayleigh fading channel using modified outage probability - Woong-Shin Kwak; Jae-Won Kim (ICT Express)
In this paper, we propose a new design metric called modified outage probability (MOP) for protograph-based low-density parity-check (LDPC) codes over the uncorrelated Rayleigh fading channel. In contrast to the conventional threshold metric, the MOP predicts the frame error rate (FER) performance accurately over the fading channel. Based on MOPs, we optimize protograph-based LDPC codes while considering the trade-off between accuracy and computational complexity. It is shown that the optimized LDPC codes outperform the conventional threshold-based LDPC codes at the FER of 10−4 for the both medium and high code-rate regions.